Reflecting Theories in Three Themes of Professional Development - Mustafa Kamal Nasution (Jurnal As-Salam, 2017)
there are three themes of professional development will be discussed in this paper; a commitment to professional development, a commitment to collaborative reflection on practice, recognizing context and culture in professional development. All Themes are elaborated respectively and relate the professional development theories to the Indonesian education system, and as a result, develop any potential understanding. All themes seem to support each other. the succeed effort of a teacher will contribute positively to their profession, in collaborative work or in the context and culture. The progress of the teacher professional development should come from the all parties’ effort. As we all know that education does not only stand alone but it is strongly influenced by the present context of politics, social, culture, or religious. In, Indonesia the advancement of this sector would strongly rely on government action rather than grassroots or professional organization initiatives. Based on the reflection, the paper proposes narrowing gaps between the universities and the schools. Implementing this direction is believed to some extent would reach certain advancement in teacher professional development in Indonesia.